The Role of Aspergillus niger in Regulating Internal Browning Involves Flavonoid Biosynthesis and the Endophytic Fungal Community of Pineapple - Fei Shen; Guang Wang; Shijiang Zhu (Journal of Fungi)
Endophytic fungi are commonly used to control plant diseases, overcoming the drawbacks of chemical agents. The internal browning (IB) of postharvest pineapple fruit, a physiological disease, leads to quality losses and limits industrial development. This work investigated the relationship among the effects of Aspergillus niger (An) on IB controlling, flavonoid metabolism and the endophytic fungal community of pineapple through metabolomics, transcriptomics, microbiomics and microorganism mutagenesis technology. We obtained an endophyte An that can control the IB of pineapple and screened its mutant strain AnM, through chemical mutagenesis, that cannot control IB. The transcriptome of fungi showed that An and AnM were different in oxidative metabolism. Transcriptome and metabolome analyses of pineapple showed that An upregulated genes of flavonoid synthesis, including dihydroflavonol 4-reductase and flavonoid 3′-monooxygenase and increased the flavonoid content in pineapple fruit, i.e., Hispidulin, Hispidulin-7-O-Glucoside, and Diosmetin, while AnM could not. Microbiomics analysis identified an increase in the abundance of eight endophytic fungi in An-inoculated fruit, among which the abundance of six endophytic fungi (Filobasidium magnum, Naganishia albida, A. niger, Aureobasidium melanogenum, Kwoniella heveanensis and Lysurus cruciatus) was positively correlated with the content of three flavonoids mentioned above but not in AnM-inoculated fruit. Overall, this suggested, for the first time, that A. niger alleviated IB mainly by enhancing flavonoid synthesis and content and the abundance of endophytic fungi and by regulating the interaction between flavonoid content and endophytic fungi abundance in pineapple. This work adds to the understanding of the IB mechanism in postharvest pineapple and provides a new green approach for reducing postharvest losses and controlling physiological diseases.